Small conductance Ca2+ -activated K+ (SK) channel mRNA expression in human atrial and ventricular tissue: comparison between donor, atrial fibrillation and heart failure tissue - Darkow, Elisa; Nguyen, Thong T.; Stolina, Marina; Kari, Fabian Alexander; Schmidt, Constanze; Wiedmann, Felix Tobias; Baczkó, István; Kohl, Peter; Rajamani, Sridharan; Ravens, Ursula; Peyronnet, Remi (Frontiers in physiology, 2021)
In search of more efficacious and safe pharmacological treatments for atrial fibrillation (AF), atria-selective antiarrhythmic agents have been promoted that target ion channels principally expressed in the atria. This concept allows one to engage antiarrhythmic effects in atria, but spares the ventricles from potentially proarrhythmic side effects. It has been suggested that cardiac small conductance Ca2+-activated K+ (SK) channels may represent an atria-selective target in mammals including humans. However, there are conflicting data concerning the expression of SK channels in different stages of AF, and recent findings suggest that SK channels are upregulated in ventricular myocardium when patients develop heart failure. To address this issue, RNA-sequencing was performed to compare expression levels of three SK channels (KCNN1, KCNN2, KCNN3) in human atrial and ventricular tissue samples from transplant donor hearts (no cardiac disease), and patients with cardiac disease in sinus rhythm or with AF. In addition, for control purposes expression levels of several genes known to be either chamber-selective or differentially expressed in AF and heart failure were determined. In atria, as compared to ventricle from transplant donor hearts, we confirmed higher expression of KCNN1 and KCNA5, and lower expression of KCNJ2, whereas KCNN2 and KCNN3 were statistically not differentially expressed. Overall expression of KCNN1 was low compared to KCNN2 and KCNN3. Comparing atrial tissue from patients with AF to sinus rhythm samples we saw downregulation of KCNN2 in AF, as previously reported. When comparing ventricular tissue from heart failure patients to non-diseased samples, we found significantly increased ventricular expression of KCNN3 in heart failure, as previously published. The other channels showed no significant difference in expression in either disease. Our results add weight to the view that SK channels are not likely to be an atria-selective target, especially in failing human hearts, and modulators of these channels may prove to have less utility in treating AF than hoped. Whether targeting SK1 holds potential remains to be elucidated.
Im Text ist "2+" und "+" jeweils hochgestellt
Gesehen am 25.05.2021